IMMUNIZATION COVERAGE OF INFANTS-RURAL-URBAN DIFFERENCE IN KERALA - T.N. Prabhakaran Nair E. Varughese (INDIAN PEDIATRICS VOLUME 31-FEBRUARY1994, 1994)
A study on the Immunization Coverage relating to the six vaccine preventable diseases was carried out in an urban, semi urban and rural area in Kerala and the results from the three areas were compared and discussed. The percentage of fully immunized children was similar in all the three areas and it was quite high. Coverage of measles vaccine was high in the Health Unit, Pangappara where health education activities were carried out by the interns. The awareness about vaccine preventable diseases was more in the urban and semiurban areas. The drop out rate for DPT and OPV was also less in urban and semiurban than in the rural areas. More than 50 per cent of the households in urban, semiurban and rural areas were unaware of the diseases prevented by DPT vaccine. Intense Health Education Campaign can definitely improve the immunization coverage further in a state which has already attained total literacy.